The development and piloting of a goals of care conversation education program for an advanced illness population. Issue 1 (2nd January 2020) - Friedman, M. Isabel; Attivissimo, Lori Ann; Kiszko, Kinga B.; Rimar, Alexander; Yezzo, Phyllis M.; Torroella Carney, Maria
ABSTRACT: Ten thousand Americans turn 65 daily. With age, individuals are confronted by complex medical modalities which can be difficult to understand and potentially burdensome. Historically, clinicians lacked the education, skill, and comfort level to identify the need for and address the patient's goals of care (GoC). Inter-professional content experts convened to develop a comprehensive program to educate and increase the comfort level of clinicians when having GoC conversations. The goal was to provide structured guidance to increase the practitioners' level of confidence in engaging patients/families in these conversations. A multimodal educational methodology using simulation was chosen as a learning strategy permitting clinicians to practice GoC conversations while receiving immediate feedback. A five hour inter-professional educational program called Goals of Care Conversation Education Program® (GoCCEP™) was developed and piloted. The GoCCEP TM 's evaluations demonstrate success giving clinicians necessary tools and a safe practice environment increasing knowledge and confidence to have substantive GoC conversations.